Effects of climate change and anthropogenic activities on lake environmental dynamics: A case study in Lake Bosten Catchment, NW China. (1st October 2022) - Tang, Xiangming; Xie, Guijuan; Deng, Jianming; Shao, Keqiang; Hu, Yan; He, Jian; Zhang, Jianping; Gao, Guang
Abstract: Arid and semiarid regions account for ∼ 40% of the world's land area. Rivers and lakes in these regions provide sparse, but valuable, water resources for the fragile environments, and play a vital role in the development and sustainability of local societies. During the late 1980s, the climate of arid and semiarid northwest China dramatically changed from "warm-dry" to "warm-wet". Understanding how these environmental changes and anthropogenic activities affect water quantity and quality is critically important for protecting aquatic ecosystems and determining the best use of freshwater resources. Lake Bosten is the largest inland freshwater lake in NW China and has experienced inter-conversion between freshwater and brackish status. Herein, we explored the long-term water level and salinity trends in Lake Bosten from 1958 to 2019. During the past 62 years, the water level and salinity of Lake Bosten exhibited inverse "W-shaped" and "M-shaped" patterns, respectively. Partial least squares path modeling (PLS-PM) suggested that the decreasing water level and salinization during 1958–1986 were mainly caused by anthropogenic activities, while the variations in water level and salinity during 1987–2019 were mainly affected by climate change. The transformation of anthropogenic activities and climate change is beneficial for sustainable freshwater management in the Lake Bosten Catchment. Our findings highlight the benefit of monitoring aquatic environmental changes in arid and semi-arid regions over the long-term for the purpose of fostering a balance between socioeconomic development and ecological protection of the lake environment. Graphical abstract: Image 1 Highlights: Water level and salinity of Lake Bosten's showed "W" and "M" shapes during 1958–2019. Climate in this basin shifted from "warm-dry" to "warm-wet" after the late 1980s. Freshwater consumption in the Lake Bosten Catchment remains stable after 1980s. After 48 years, Lake Bosten transitioned from brackish back to freshwater in 2019. Uncertainty from climate change potentially poses a threat on Lake Bosten's sustainability.